Fifty Years of U.S. Income Data from the Current Population Survey: Alternatives, Trends, and Quality - Weinberg, Daniel H; Nelson, Charles T; Roemer, Marc I; Welniak, Edward J (American Economic Review, 1999)
Fifty Years of U.S. Income Data from the Current Population Survey: Alternatives, Trends, and Quality by Daniel H. Weinberg, Charles T. Nelson, Marc I. Roemer and Edward J. Welniak. Published in volume 89, issue 2, pages 18-22 of American Economic Review, May 1999